Etiology and pathophysiology of tendon ruptures in sports - Kannus, P.; Natri, A. (Scandinavian Journal of Medicine & Science in Sports, 1997)
Of all spontaneous tendon ruptures, complete Achilles tendon tears are most closely associated with sports activities (1-3). Schonbauer (3) reported that 75% of all ruptures of the Achilles tendon are related to sports. In Plecko & Passl (2) the number was 60%. In our material of 430 cases, the number of sports-related Achilles ruptures was very similar (62%), while only 2% of ruptures of other tendons were sports-related (P < 0.001) (1). Also, the majority of Achilles reruptures occurred in sports. The ruptures occurred most often in soccer (34%), track and field (16%) and basketball (14%). The distribution of Achilles ruptures according to different sports varies considerably from country to country, according to the national sport traditions. For example, in northern and middle Europe, soccer, tennis, track and field, indoor ball games, downhill skiing, and gymnastics are the most common; and in North America, football, basketball, baseball, tennis and downhill skiing dominate the statistics (1, 2, 4). In sports, some Achilles ruptures are not spontaneous or degeneration-induced but may occur as a consequence of the remarkably high forces that are involved in the performance (2). Ruptures in the high jump or triple jump are good examples. In such cases, failure in the neuromuscular protective mechanisms due to fatigue or disturbed co-ordination can frequently be found. The spontaneous complete rupture of the supraspinatus tendon of the rotator cuff does not occur very frequently in sports. Those sports that include high-energy throwing movements, such as American and Finnish baseball, American football, rugby and discuss and javelin throwing, may, however, produce this injury. Partial tears and inflammations of the rotator cuff complex are much more frequent in throwing sports. The complete rupture of the proximal long head of the biceps brachii tendon is rare among competitive and recreational athletes. In our material, under 2% of these ruptures were associated with sports activities (5). The rupture (avulsion) of the distal tendon of the biceps muscle is rare. In sports, gymnastics, body building and weight lifting have been said to be able to produce this injury (6). In general, complete ruptures of the quadriceps tendon and the patellar tendon occur most often in older individuals. In our study, the mean age of these patients was 65 years (5). However, these injuries do also occur in younger age groups, especially in athletes. In athletes, the rupture most frequently occurs in high-power sports events, such as high jump, basketball and weight lifting, at the age of 15-30 years. A chronic-patellar apicitis (jumper's knee) may predispose rupture of the tendon (7). As is the case with the rotator cuff complex, overuse inflammation and partial tears of the quadriceps and patellar tendons are one of the most characteristic athletic injuries. Complete spontaneous ruptures of other tendons in sports are rare, although the literature does provide case studies from almost every tendon the human body possesses (8-18).